Administration of Oral Contraceptives Could Alleviate Age-Related Fertility Decline Possibly by Preventing Ovarian Damage in a Mouse Model. (September 2018) - Isono, Wataru; Wada-Hiraike, Osamu; Kawamura, Yumiko; Fujii, Tomoyuki; Osuga, Yutaka; Kurihara, Hiroki
Age-related fertility decline is hypothesized to occur mainly by the spontaneous exhaustion and deterioration of the ovarian follicle, and the accumulation of ovarian tissue damage resulting from the ovulation cycle may play roles in the process. In this study, we hypothesized that suppressing ovulation would exert protective effects against age-related fertility decline. To test this hypothesis, we established a mouse model in which oral contraceptives (OCs) were administered daily. Female C57BL/6N mice were administered OCs daily from the age of 2 months to 12 months as an ovulation suppression mouse model. Mouse fecundity was investigated by counting oocyte number after ovarian stimulation and by examining live fetuses after mating. We found that compared with control mice administered vehicle alone, 12-month-old mice administered 2-fold dose OCs used for treating humans exhibited a significantly greater average oocyte number after ovarian stimulation (8.5 ± 0.6 vs 5.9 ± 0.6, P < .01). In addition, spontaneous conception with living fetuses after mating was strikingly increased in 12-month-old mice administered OCs relative to controls (6.0 ± 1.2 vs 0.4 ± 0.3, P < .01). In the histological examination of mouse ovarian tissues, we did not detect a significant difference in ovarian follicle number, but reduced amount of brownish foamy fibrous tissues, which might reflect ovarian tissue damage, was detected in aged mice administered OCs. These results suggest the possibility that long-term OC administration might alleviate age-related fertility decline, and the improvement mechanism could be attributed to the prevention of ovarian tissue damage by suppressing ovulation.